What Determines Cognitive Functioning in the Oldest-Old? The EMIF-AD 90+ Study. (8th September 2020) - Legdeur, Nienke; Badissi, Maryam; Yaqub, Maqsood; Beker, Nina; Sudre, Carole H; ten Kate, Mara; Gordon, Mark Forrest; Novak, Gerald; Barkhof, Frederik; van Berckel, Bart N M; Holstege, Henne; Muller, Majon; et al.
Abstract: Objectives: Determinants of cognitive functioning in individuals aged 90 years and older, the oldest-old, remain poorly understood. We aimed to establish the association of risk factors, white matter hyperintensities (WMHs), hippocampal atrophy, and amyloid aggregation with cognition in the oldest-old. Method: We included 84 individuals without cognitive impairment and 38 individuals with cognitive impairment from the EMIF-AD 90+ Study (mean age 92.4 years) and tested cross-sectional associations between risk factors (cognitive activity, physical parameters, nutritional status, inflammatory markers, and cardiovascular risk factors), brain pathology biomarkers (WMH and hippocampal volume on magnetic resonance imaging, and amyloid binding measured with positron emission tomography), and cognition. Additionally, we tested whether the brain pathology biomarkers were independently associated with cognition. When applicable, we tested whether the effect of risk factors on cognition was mediated by brain pathology. Results: Lower values for handgrip strength, Short Physical Performance Battery (SPPB), nutritional status, HbA1c, and hippocampal volume, and higher values for WMH volume and amyloid binding were associated with worse cognition. Higher past cognitive activity and lower body mass index were associated with increased amyloid binding, lower muscle mass with more WMH, and lower SPPB scores with more WMH and hippocampal atrophy. The brain pathology markers were independently associated with cognition. The association of SPPB with cognition was partially mediated by hippocampal volume. Discussion: In the oldest-old, physical parameters, nutritional status, HbA1c, WMH, hippocampal atrophy, and amyloid binding are associated with cognitive impairment. Physical performance may affect cognition through hippocampal atrophy. This study highlights the importance to consider multiple factors when assessing cognition in the oldest-old.